(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2022)
The characteristics of self-healing related to N-type cement mortars, the addition of human pathological bacteria to enhance mortar durability, and compressive strength thus reducing maintenance cost and manpower after crack initiation. Bacteria have been examined by using two types of biological agents: Proteus mirabilis and E. Coli bacteria. Mortars are formed from a combination of Portland cement and ordinary sand, treated by Proteus mirabilis and E. Coli bacteria with different concentrations. The mechanical properties of the treated mortars are measured and the mortars were characterized by means of Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and electron energy dispersive spectroscopy (EDX). This study shows that Proteus mirabilis and E. Coli assist the formation of calcium carbonate inside the mortar micro-pores leading to enhancement of the compressive strength and hardness of the mortar specimen. This emphasizes the possibility of activating the self-healing characteristic of the cement mortar and its utilization for cracks treatment and repair